The Effect of Education Through Animated Videos on Knowledge of Diabetes Mellitus Risk in Adolescents with Obesity at SMK Negeri 3 Gorontalo City - Srilestari R. Rijib; Ita Sulistiani Basir; Cindy Puspita Sari Haji Jafar (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Obesity is a global problem that affects every country. In the same year, about 2.5 billion adults were overweight, and 890 million of them were living with obesity. Since 1990, the prevalence of obesity has more than tripled and overweight has increased by more than 1.5 times. The type of research used in this study is a type of quantitative research with a quasi-experimental design, using a pretest-postest approach with control group design, to determine the difference in knowledge of diabetes mellitus risk in the group that was given animated video education and the group that was given education using the usual lecture method. The results of the pretest showed that the level of knowledge of respondents in the experimental group was only 8 respondents (47.1%), the category was less than 5 respondents (29.4), the good category was 4 respondents (23.5%) in the control group of the category was 7 respondents (41.2%), the good and poor categories were 5 respondents each (29.4%). The results of the posttest showed that all respondents in the experimental group and the control group had a level of knowledge in the good category, as many as 17 respondents (100%) each. There is an effect of education through animated videos on knowledge of the risk of diabetes mellitus in obese adolescents at SMK Negeri 3 Gorontalo City, which is proven by the results of the Wilcoxon Signed Rank Test with a p-value = 0.000 (p < 0.05).